2019
DOI: 10.3386/w25796
|View full text |Cite
|
Sign up to set email alerts
|

Can Successful Schools Replicate? Scaling Up Boston’s Charter School Sector

Abstract: NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 22 publications
6
33
0
Order By: Relevance
“…But the track record for charter lottery estimates is encouraging. In addition to the fact that lottery estimates have been replicated in many large urban districts, Cohodes, Setren, and Walters (2016) showed that a recent wave of Boston charter expansions, a policy innovation prompted by a legislative change, produced achievement gains very much in line with earlier lottery estimates.…”
Section: Summary and Directions For Further Workmentioning
confidence: 73%
“…But the track record for charter lottery estimates is encouraging. In addition to the fact that lottery estimates have been replicated in many large urban districts, Cohodes, Setren, and Walters (2016) showed that a recent wave of Boston charter expansions, a policy innovation prompted by a legislative change, produced achievement gains very much in line with earlier lottery estimates.…”
Section: Summary and Directions For Further Workmentioning
confidence: 73%
“…This raises additional challenges in terms of identification. Ample evidence shows that charter students differ from non-charter students and that this selection changes when charter schools expand (Epple et al, 2015;Baude et al, 2014;Cohodes et al, 2016). Restricting achievement outcomes to non-charter students, as we do for expenditures outcomes, would bias estimations.…”
Section: Introductionmentioning
confidence: 88%
“…The federal Investing in Innovation program provided grants to applicants shown to have improved student achievement and attainment, including about $70 million to five charter school networks between 2010 and 2016 . Finally, states such as Massachusetts have passed legislation limiting growth in the charter sector to networks with evidence of success (Cohodes et al., ). This approach of targeting support to successful networks involves a trade‐off, as it may limit innovation in the charter sector.…”
Section: Have Lessons From Charter Schools Been Applied Elsewhere?mentioning
confidence: 99%
“…In Boston, the lifting of a cap on charters doubled their concentration from 16 to 31 percent of students. New charter schools opened during this period remained effective, and the overall effectiveness of Boston's charter sector increased (Cohodes, Setren, & Walters, ). Tuttle et al.…”
Section: Can We Learn More From the Charter School Experiment?mentioning
confidence: 99%